Impaired vasocontractile responses to adenosine in chorionic vessels of human term placenta from pregnant women with pre-existing and gestational diabetes - Razak, Azlina A.; Leach, Lopa; Ralevic, Vera (Sage, 2018)
Background: There is clinical and experimental evidence for altered adenosine signalling in the fetoplacental circulation in pregnancies complicated by diabetes, leading to adenosine accumulation in the placenta. However, the consequence for fetoplacental vasocontractility is unclear. This study examined contractility to adenosine of chorionic vessels from type 1 diabetes mellitus, gestational diabetes mellitus and normal pregnancies. Methods: Chorionic arteries and veins were isolated from human placenta from normal, gestational diabetes mellitus and type 1 diabetes mellitus pregnancies. Isometric tension recording measured responses to adenosine and the thromboxane A2 analogue U46619 (thromboxane A2 mediates adenosine fetoplacental vasoconstriction). Adenosine and thromboxane prostanoid receptor protein expression was determined by immunoblotting. Results: Adenosine elicited contractions in chorionic arteries and veins which were impaired in both gestational diabetes mellitus and type 1 diabetes mellitus. Contractions to potassium chloride were unchanged. Adenosine A2A and A2B receptor protein levels were not different in gestational diabetes mellitus and normal pregnancies. Contractions to U46619 were unaltered in gestational diabetes mellitus arteries and increased in type 1 diabetes mellitus arteries. Overnight storage of vessels restored contractility to adenosine in gestational diabetes mellitus arteries and normalized contraction to U46619 in type 1 diabetes mellitus arteries. Conclusion: These data are consistent with the concept of aberrant adenosine signalling in diabetes; they show for the first time that this involves impaired adenosine contractility of the fetoplacental vasculature.